ALGORITHMIZATION OF PROBLEMS FOR OPTIMAL LOCATION OF TRANSFORMERS IN SUBSTATIONS OF DISTRIBUTED NETWORKS - M. I. Fursanov; N. S. Petrashevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
This article reflects algorithmization of search methods of effective replacement of consumer transformers in distributed electrical networks. As any electrical equipment of power systems, power transformers have their own limited service duration, which is determined by natural processes of materials degradation and also by unexpected wear under different conditions of overload and overvoltage. According to the standards, adapted by in the Republic of Belarus, rated service life of power transformers is 25 years. But it can be situations that transformers should be better changed till this time – economically efficient. The possibility of such replacement is considered in order to increase efficiency of electrical network operation connected with its physical wear and aging.In this article the faults of early developed mathematical models of transformers replacement were discussed. Early such worked out transformers were not used. But in practice they can be replaced in one substation but they can be successfully used  in other substations .Especially if there are limits of financial resources and the replacement needs more detail technical and economical basis.During the research the authors developed the efficient algorithm for determining of optimal location of transformers at substations of distributed electrical networks, based on search of the best solution from all sets of displacement in oriented graph. Suggested algorithm allows considerably reduce design time of optimal placement of transformers using a set of simplifications. The result of algorithm’s work is series displacement of transformers in networks, which allow obtain a great economic effect in comparison with replacement of single transformer.